Minimal Impact of COVID-19 Pandemic on the Mental Health and Wellbeing of People Living With Dementia: Analysis of Matched Longitudinal Data From the IDEAL Study - Sabatini, Serena; Bennett, Holly Q.; Martyr, Anthony; Collins, Rachel; Gamble, Laura D.; Matthews, Fiona E.; Pentecost, Claire; Dawson, Eleanor; Hunt, Anna; Parker, Sophie; Allan, Louise; Burns, Alistair; et al. (Frontiers in Psychiatry, 2022)
Objective: Research suggests a decline in the mental health and well-being of people with dementia (PwD) during the COVID-19 pandemic; however few studies have compared data collected pre-pandemic and during the pandemic. Moreover, none have compared this change with what would be expected due to dementia progression. We explored whether PwD experienced changes in mental health and well-being by comparing pre-pandemic and pandemic data, and drew comparisons with another group of PwD questioned on two occasions prior to the pandemic. Methods: Community-dwelling PwD enrolled in the IDEAL programme were split into two groups matched for age group, sex, dementia diagnosis, and time since diagnosis. Although each group was assessed twice, one was assessed prior to and during the pandemic (pandemic group; n=115) whereas the other was assessed prior to the pandemic (pre-pandemic group; n=230). PwD completed measures of mood, sense of self, well-being, optimism, quality of life, and life satisfaction. Results: Compared to the pre-pandemic group, the pandemic group were less likely to report mood problems, or be pessimistic, but more likely to became dissatisfied with their lives. There were no changes in continuity in sense of self, well-being, and quality of life. Discussion: Results suggest the pandemic had little effect on the mental health and well-being of PwD, with any changes observed likely to be consistent with expected rates of decline due to dementia. Although personal accounts attest to the challenges experienced, PwD appear to have been resilient to the impact of lockdown and social restrictions during the pandemic.